A proteção do meio ambiente no comércio internacional: compatibilização de políticas públicas com o direito internacional - Zanocchi, José Maria McCall (2013)
This paper focuses on the complex interaction between international trade and the environment, with emphasis on the consistency of environmental policies that interfere with the economic activity under a wider perspective of the avant-garde of international law. The matter is analyzed under a multidisciplinary approach involving history, economics, ecology, international relations and current affairs, including the system of rules governing international trade and international law itself. With these ingredients, the work is developed with recourse to an extensive bibliographic review of the related issues, specially the foreign doctrine, more advanced on its specific object, as well as, on a more ample standard, the sources of law with international projection or repercussion, the laws and existing precedents in terms of customary law and jurisprudence. Initially, the investigation turns to the roots of the historical division between developed and developing countries, and its consequences, to correlate it with the most recent trends of the current international order, with the project of a global society of the 21st century set forth under ideals of fundamental rights that interrelate in the world. The environmental thematic rises in that context, evolving from the dawn of the ecological awareness to the transversal goal of sustainable development, with diverse implications and developments. As to that aspect it is shown how the legal science has evolved to face such paradigms and its reflexes on the current international law system, building the bases for an authentic international environmental order. Under the challenge of the sustainable development, the international trade is seen as a paradoxical vector, for the bad or for the good, what gives place to claims for its adjustment on more equitable and fair grounds, mainly in relation to the system of rules under the World Trade Organization. The objective, in the end, will be to demonstrate in what conditions the international trade may promote sound environmental policies with transnational projections, being compatible with international law, so as to consecrate a free, open and stable multilateral trade system that allows economic development without compromising the environmental quality of the planet.